Strategic analysis of net exchanges in professional padel: insights from different competition phases of the World Padel Tour Finland Padel Open Tournament - Escudero-Tena, A.; Conde-Ripoll, R.; Lupo, C.; Ungureanu, A. N. (International Journal of Sports Physiology and Performance, 2024)
Purpose: This study analyzed the effectiveness of net exchanges (ie, number of times the pairs exchange their zone on the court from the net zone to the back zone or vice versa) in men`s and women`s professional padel depending on the competition phase.